Waterborne parasites: a current status from the Philippines - Onichandran, S.; Kumar, T.; Salibay, C.C.; Dungca, J.Z.; Tabo, H.A.L.; Tabo, N.; Tan, Tian Chye; Lim, Yvonne Ai Lian; Sawangjaroen, N.; Phiriyasamith, S.; Andiappan, H.; Ithoi, Init; et al. (BMC, 2014)
Background: Despite the amount of awareness created, waterborne disease still poses threat, especially in developing countries. Due to the scarcity of reported data on waterborne parasites, the consumption of unsafe water prolongs. Thus, the occurrences of waterborne parasites from various samples were investigated from one of the Southeast Asian country, the Philippines.